2018
DOI: 10.1080/15230430.2018.1475951
|View full text |Cite
|
Sign up to set email alerts
|

Side by side? Vascular plant, invertebrate, and microorganism distribution patterns along an alpine to nival elevation gradient

Abstract: High mountain areas above the alpine zone are, despite the low-temperature conditions, inhabited by evolutionary and functionally differing organism groups. We compared the abundance and species richness of vascular plants, oribatid mites, springtails, spiders, and beetles, as well as bacterial and methanogenic archaeal prokaryotes (only abundance), at 100 m vertical intervals from 2,700-3,400 m in the Central Alps. We hypothesized that the less mobile microarthropods and microorganisms are more determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
5
9
0
Order By: Relevance
“…This result is in agreement with carabid species richness patterns investigated in other mountain areas (e.g. Maveety, Browne, & Erwin, ; Winkler et al, ; Zou, Sang, Zhou, Huang, & Axmacher, ). Our results highlighted that the studied species traits (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…This result is in agreement with carabid species richness patterns investigated in other mountain areas (e.g. Maveety, Browne, & Erwin, ; Winkler et al, ; Zou, Sang, Zhou, Huang, & Axmacher, ). Our results highlighted that the studied species traits (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of different patterns for different taxonomical groups in the same region are in line with the results of Winkler et al [ 74 ], who showed that the abundance of beetles and spiders was affected by elevation in the Central Alps, while this was not the case in springtails and oribatid mites. In our study, millipede abundance showed no significant pattern with elevation.…”
Section: Discussionsupporting
confidence: 93%
“…The trend of beetle decline was in line with other studies [6,63]. The sharp decline in beetles has been recorded in a similar situation in European countries [64]. Reductions in the abundance and richness of carabids were partly attributed to natural evolution [65], which cannot be clearly separated from time-related effects, e.g., structural disturbances [66].…”
Section: Discussionsupporting
confidence: 88%